2022
DOI: 10.1249/mss.0000000000002962
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Physiological Responses to Ultramarathon

Abstract: Purpose: Despite a growing body of literature on the physiological responses to ultramarathon, there is a paucity of data in females. This study assessed the female physiological response to ultramarathon and compared the frequency of perturbations to a group of race-and time-matched males. Methods: Data were collected from 53 contestants of an ultramarathon trail race at the Ultra-Trail du Mont-Blanc (UTMB®) in 2018/19. Before and within 2 h of the finish, participants underwent physiological assessments, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
(81 reference statements)
0
9
0
1
Order By: Relevance
“…In contrast, two studies involving shorter distances (55 km or 70 km) reported a lower incidence of ECHO changes indicative of cardiac fatigue in females [ 39 , 40 ]. Tiller et al measured stroke volume and cardiac output before and after a 171 km race and reported the only significant change to be an increase in cardiac output in females [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, two studies involving shorter distances (55 km or 70 km) reported a lower incidence of ECHO changes indicative of cardiac fatigue in females [ 39 , 40 ]. Tiller et al measured stroke volume and cardiac output before and after a 171 km race and reported the only significant change to be an increase in cardiac output in females [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Females: only reduced LV dimension ( p = 0.05) and increased RV diameter ( p = 0.012) were significant Picco et al[ 40 ] 24 athletes (5 females aged 38 ± 4 years, and 19 males aged 42 ± 12 years) who completed a 55 km mountain ultramarathon ECHO, serum lactate and CPK Cohort study Low Females had lower incidence of ECHO features of exercise induced cardiac fatigue for the right ventricle ( p = 0.3) and the left ventricle ( p < 0.001) Females had significantly lower serum lactate post-race (2.63 mmol/L vs 4.37 mmol/L, p = 0.018). No difference in CPK Cote et al[ 41 ] 25 athletes (8 females aged 45.9 ± 10.2 years, and 17 males aged 44.8 ± 6.6 years) who completed either a 100 km or 160 km ultramarathon ECHO Cohort study Low No significant sex differences in the cardiac response to an ultramarathon Tiller et al[ 42 ] 16 athletes (8 females and 8 performance-matched males) who completed either the UTMB or CCC races in 2018 or 2019. Average age 38.4 ± 7.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…В дополнение к этому в исследовании N. Tiller с соавт. также отметили более выраженные нарушения физиологии сердечно-сосудистой системы у мужчин, чем у женщин, после ультрамарафона [59]. Потенциально данные негативные эффекты могли привести к большему высвобождению сердечных тропонинов у мужчин, по сравнению с лицами женского пола.…”
Section: возможные механизмы формирования гендерных особенностей серд...unclassified